PENERAPAN AKUNTANSI SAK EMKM DALAM PENYUSUNAN LAPORAN KEUANGAN UMKM DI KOTA PEKANBARU - Nuraini, Nuraini; Piliang, Arfah; Alqorni, Nisa; Irawan, Candra; Rasmon, Rasmon (Jurnal Akuntansi Kompetif, 2025)
The purpose of this study is to find out whether MSMEs in Binawidya District, Pekanbaru City have implemented SAK EMKM in compiling financial statements. The researcher used purposive sampling in obtaining research samples. Where the informants involved in this study are MSME owners/managers consisting of 35 business actors. Data collection was carried out by interview and documentation techniques. The result of this study is that the MSMEs studied have not implemented SAK EMKM in the preparation of financial statements. MSME actors only make business activity reports consisting of recording income and expenses in accordance with the understanding of each MSME owner.